Modelling the Impact of the Digital Economy on the Development of the Logistics Industry. Study Case of Henan Province - OROZONOVA, Azyk; ZHANG, Shanshan; ZHUMADILOV, Esengeldi; SUN, Xiaomei; LIU, Xueqing (Theoretical and Practical Research in Economic Fields, 2024)
The purpose of the study is to model and analyse the impact of the digital economy on the development of the logistics industry in Henan province. To achieve this goal, the following methods were used: historical analysis to determine the stages of digitalisation of logistics, statistical analysis to assess the dynamics of gross domestic product (GDP) by economic sectors, system analysis and analysis of strengths, weaknesses, opportunities and threats to investigate the impact of individual elements of the digital economy on the logistics sector, and regression analysis to model the relationships between digitalisation and economic indicators of the logistics industry in Henan province. The main results of the study were: identification and analysis of key stages in the development of the logistics industry in China; determination of structural changes in the GDP of Henan province and their correlation with trends in the digital economy; development of a regression model demonstrating the dependence of economic growth in the tertiary sector of the economy, including the logistics industry, on the advancement of digital technologies. The study confirmed the hypothesis of a significant impact of the digital economy on the logistics sector of Henan province, which is reflected in quantitative estimates and confirmed by statistical tests.